2013
DOI: 10.1111/bdi.12061
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive features in subgroups of bipolar disorder

Abstract: ObjectiveTo examine which subgroups of DSM-IV bipolar disorder (BD) [BD type I (BD-I) or BD type II (BD-II), and subgroups based on history of psychosis, presenting polarity, and age at onset] differentiate best regarding neurocognitive measures.MethodsA total of 199 patients with BD were characterized by clinical and neurocognitive features. The distribution of subgroups in this sample was: BD-I, 64% and BD-II, 36%; 60% had a history of psychosis; 57% had depression as the presenting polarity; 61% had an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 76 publications
3
35
1
4
Order By: Relevance
“…The authors confirmed cognitive impairments in euthymic BP, but found considerably lower effect sizes (d =.26-.63) than previous meta-analyses (d= .5-1). In line with this result, other studies reported that only a part of their bipolar sample had significant cognitive impairments (Altshuler et al, 2004;Aminoff et al, 2013;Iverson et al, 2011;Martino et al, 2008). Thus, there seem to be subgroups within the cluster of BD; however, the underlying reasons are unclear: Some patients do not reach their former level of cognitive performance and become more disabled with progressing illness, while others remit completely after each episode and maintain a high occupational and social functioning (Gilbert and Marwaha, 2013).…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…The authors confirmed cognitive impairments in euthymic BP, but found considerably lower effect sizes (d =.26-.63) than previous meta-analyses (d= .5-1). In line with this result, other studies reported that only a part of their bipolar sample had significant cognitive impairments (Altshuler et al, 2004;Aminoff et al, 2013;Iverson et al, 2011;Martino et al, 2008). Thus, there seem to be subgroups within the cluster of BD; however, the underlying reasons are unclear: Some patients do not reach their former level of cognitive performance and become more disabled with progressing illness, while others remit completely after each episode and maintain a high occupational and social functioning (Gilbert and Marwaha, 2013).…”
Section: Introductionmentioning
confidence: 55%
“…Unfortunately, many previous studies did not report criteria for the duration of euthymic mood in their samples, or did not control for sub-depressive symptoms (Bombin et al, 2013;Ryan et al, 2012;Thompson et al, 2005) which might well account for discrepancies in the published literature. Some investigations reported high depression scores in their samples and therefore included more symptomatic patients, which could be responsible for larger effects (Aminoff et al, 2013;Chaves et al, 2011;Levy et al, 2013). Other studies conducted neuropsychological tests after a very short period of remission, which is still a relatively unstable state (Brissos et al, 2011;Dittmann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations